The impact of mindfulness meditation on social and moral behavior: Does mindfulness enhance other-oriented motivation or decrease monetary reward salience? - Feruglio, Susanna; Panasiti, Maria Serena; Crescentini, Cristiano; Aglioti, Salvatore Maria; Ponsi, Giorgia (Frontiers in Integrative Neuroscience, 2022)
This perspective article provides an overview of the impact of mindfulness meditation (MM) on social and moral behavior. In mindfulness research, prosocial behavior has been operationalized as helping behavior, altruistic redistribution of funds, reparative behavior or monetary donation. Studies concerning moral behavior are still scarce. Despite inconsistent evidence, several studies found a beneficial effect of mindfulness on prosocial outcomes (i.e., a higher propensity to spend or give away money for the sake of other individuals). However, since the employed tasks were reward-based, participants’ decisions directly affected also their own payoff, by reducing it. Crucially, MM also affects self-control circuitry and reduces reward-seeking behaviors and reward salience, by making rewards less tempting. We discuss evidence suggesting how challenging may be to dissociate the specific weight of enhanced other-oriented motivation from the one of decreased monetary reward salience in explaining meditators’ behavior. Future higher quality studies are needed to address this open issue.